The factors causes of LBWI in RSUD Wates Kulon Progo 2017-2018 - Ayu Damayanti; Nanik Setiyawati; Margono Margono (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
Background: Based on WHO and UNICEF data, in 2013 around 22 million babies were born in the world, of which 16% were born with low birth weight and contributed 60-80% of the total neonatal deaths. According to Riskesdas 2018 the average LBW in Indonesia is 6.2% and LBW in DIY amounting to 8.2, the percentage of LBW in DIY in 2017 is 4.86%. The highest area of LBW is Kulon Progo Regency 6.69%, and in Wates RSUD Kulon Progo Regency in 2017-2018 there are as many as 554 who experience LBW. The Objectives: To find out the causes of LBW incidence in Wates Hospital Kulon Progo Regency in 2017-2018 The Method: This study uses a case-control design. The population in this study were all of mothers who gave birth and their babies were treated in Wates Hospital which was recorded in the medical record at Wates Hospital. Data is taken from the patient's medical record. The sampling technique used was purposive sampling. The sample is 152 samples, consisting of 76 cases and 76 controls. There are external variants analyzed, namely maternal age, parity, Hb level, nutritional status, birth distance, pre-eclampsia history, history of antepartum bleeding and LBW history. The data analysis was in a univariate, bivariate using Chi-square test, and multivariate used logistic regression. The Results: Chi-square analysis results obtained a value (p <0.05) which showed a significant relationship including maternal age p = 0.011 (OR 3.046 CI95% 1.338-6.933), Hemoglobin level p = 0.043 (OR 2.303 CI95% 1.089-4.870 ), nutritional status p = 0.49 (OR 2.188 CI95% 1.063-4.503), history of pre-eclampsia p = 0.032 (OR 2.564 CI95% 1.147-5.735), history of LBW p = 0.007 (OR 4.407 CI95% 1,542-12,591) with the incidence of LBW, and there was no relationship between parity, birth distance and history of antepartum bleeding with the incidence of LBW. Conclusion: There is a relationship between maternal age, Hemoglobin level, nutritional status, pre-eclampsia history, LBW history.